Enzyme technology in food preservation: A promising and sustainable strategy for biocontrol of post-harvest fungal pathogens - da Silva, Ronivaldo Rodrigues [UNESP] (My University, 2019)
Population aging has reinforced the need for production of foods with high nutritional value, especially fresh fruits and vegetables. In general, due to their perishable nature, these foods are prone to spoilage by post-harvest microorganisms. For this reason, I aim to discuss in this article the alternative use of enzymes as biocontrol agents against fungal infections in post-harvest fruits and vegetables. This article therefore proposes a sustainable alternative with demonstrated success to improve the preservation of food in its fresh form and facilitating its storage, mainly in domestic space. Food spoilage caused by microorganisms has adverse economic effects. Pathogens such as Monilinia spp., Botrytis cinerea, and Penicillium expansum are important fungi that cause post-harvest spoilage of fruits.Thus, the application of enzymes in food chemistry offers a promising approach to improve the shelf life of foods without altering the organoleptical characteristics and nutritional content.
Keywords: Chitinase; Food spoilage; Microbial enzyme; Mold; Proteolytic enzymes